AIDS Cholangiopathy in an Asymptomatic, Previously Undiagnosed Late-Stage HIV-Positive Patient from Kenya - Yiming Gao; Kathryn Chin; Yehia Y. Mishriki (International Journal of Hepatology)
AIDS-associated cholangiopathy is a form of biliary tract inflammation with stricture formation seen in AIDS patients who are severely immunosuppressed. It is no longer common in countries in which HAART therapy is widely employed but is still seen in underdeveloped countries. The majority of patients are symptomatic at the time of presentation. Herein, we describe a seventy-four-year-old woman who presented with unilateral leg swelling after a prolonged airplane flight. She was otherwise entirely asymptomatic. Routine laboratory testing was notable for a hypochromic microcytic anemia, slight leukopenia, and mild hypoalbuminemia. Liver enzymes were all elevated. Deep venous thrombosis was confirmed, and a CT scan of the chest disclosed no pulmonary emboli. However, the visualized portion of the abdomen showed dilatation of the common bile and pancreatic ducts. This was confirmed on ultrasonography and MRCP, and no obstructive lesions were noted. An ERCP revealed a dilated common bile duct without filling defects or strictures. A balloon occlusion cholangiogram showed strictures and beading of the intrahepatic ducts. Shortly thereafter, serology for HIV returned positive along with a depressed CD4 cell count, and the patient was diagnosed with AIDS-associated cholangiography.